Variants in tropomyosins TPM2 and TPM3 causing muscle hypertonia - Wallgren-Pettersson, Carina (Pergamon Press, 2025)
Patients with myopathies caused by pathogenic variants in tropomyosin genes TPM2 and TPM3 usually have muscle hypotonia and weakness, their muscle biopsies often showing fibre size disproportion and nemaline bodies. Here, we describe a series of patients with hypercontractile molecular phenotypes, high muscle tone, and mostly non-specific myopathic biopsy findings without nemaline bodies. Three of the patients had trismus, whilst in one patient, the distal joints of her fingers flexed on extension of the wrists. In one biopsy from a patient with a rare TPM3 pathogenic variant, cores and minicores were observed, an unusual finding in TPM3-caused myopathy. The variants alter conserved contact sites between tropomyosin and actin.